Conservation Strategies in Cultural Heritage: Literature Perspectives on Repair and Preservation Techniques (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The conservation of cultural heritage is essential for preserving historical and cultural artefacts, especially against environmental, technical, and socio-political threats. This overview examines modern conservation efforts, emphasising repair and preservation methods, and showcasing advancements in material science, environmental practices, and ethical considerations. The research presented here analyses studies from 2020 to 2024 to identify upcoming trends, including nanotechnology and digital documentation, and explores the consequences of these developments for global heritage management. The paper examines the convergence of conservation ethics with community involvement, highlighting the significance of participatory methods. Research indicates a necessity for interdisciplinary cooperation and targeted funding to improve the efficacy and accessibility of conservation initiatives.